2010
DOI: 10.1161/circoutcomes.109.890707
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events After Stopping Clopidogrel in Post–Acute Coronary Syndrome Patients

Abstract: Background-A prior study from the Veterans Health Administration found a clustering of cardiovascular events after clopidogrel cessation. We sought to confirm and expand these findings. Methods and Results-This was a retrospective cohort study of 2017 patients with acute coronary syndrome discharged on clopidogrel from an integrated health care delivery system. Rates of all-cause mortality or acute myocardial infarction (MI) within 1 year after stopping clopidogrel were assessed among patients who did not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 16 publications
1
51
0
3
Order By: Relevance
“…However, prior studies have demonstrated that gaps in both prescription and use of secondary prevention medications, such as clopidogrel, at hospital discharge, are often magnified rather than reduced in the outpatient setting. 13,14 Second, incomplete or inaccurate documentation of clopidogrel contraindication could cause our characterization of a gap to be overstated. However, data abstraction for the ACTION Registry-GWTG is subject to data quality methods, which minimizes this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have demonstrated that gaps in both prescription and use of secondary prevention medications, such as clopidogrel, at hospital discharge, are often magnified rather than reduced in the outpatient setting. 13,14 Second, incomplete or inaccurate documentation of clopidogrel contraindication could cause our characterization of a gap to be overstated. However, data abstraction for the ACTION Registry-GWTG is subject to data quality methods, which minimizes this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of ischemic effects following cessation of P2Y 12 inhibitors has been described [17][18][19] and "rebound" platelet hyperreactivity after discontinuation of thienopyridines has been proposed to explain it. While it is not surprising that platelet reactivity increases relative to reactivity while on treatment with thienopyridines (i.e.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Des observations [165,166] similaires sont rapportées avec un arrêt prématuré ou inaproprié du clopidogrel.…”
Section: Arrêt Ou Maintien Du Traitement Par Agent Antiplaquettaire ?unclassified
“…Une hémostase chirurgicale simple associant hémostatique local et sutures permet de contrôler efficacement le risque de saignement péri-opératoire. Par ailleurs, des études [165,166] ont montré chez des patients porteurs de stents, la survenue d'événement thrombotique dans une période de 1 à 3 mois suite à l'arrêt de la bithérapie (arrêt du clopidogrel et poursuite de l'aspirine). Ceci soulève la question d'un possible « phénomène de rebond prothrombotique » à l'arrêt du clopidogrel [257], effet délétère également évoqué avec l'aspirine [60,102,103] mais dont la physiopathologie n'est toujours pas élucidée [18].…”
Section: Arrêt Ou Maintien Du Traitement Par Agent Antiplaquettaire ?unclassified